Lectures on philosophical ethics - Schleiermacher, Friedrich, 1768-1834 (Cambridge texts in the history of philosophy., 2002)
Schleiermacher is known to English readers primarily as a theologian and hermeneuticist, but many German scholars have argued that it is in fact his philosophical work in ethics that constitutes his most outstanding intellectual achievement. This edition also includes a historical and philosophical introduction and notes on further reading.